The MCC Compact in Nepal: Potential Benefits, Complexities and Implementation Challenges - Phuyel, Shyam Prasad (Randwick International of Social Science Journal, 2025)
ABSTRACT This study examines the difficulties of Nepal's agreement with the Millennium Challenge Corporation (MCC). It incorporates a major financial commitment of both the US and the government of Nepal, with the prime focus on multiple areas. Yet, the implementation of MCC in Nepal has caused a number of controversies associated with national sovereignty, security, and its visible supremacy over the Nepalese constitution, effects on geopolitics, specially the United States' Indo-Pacific Strategy and China's growing influence in Nepal. This study encompasses a qualitative research design with secondary data sources. Descriptive analysis is used to examine and study the political, social, and strategic aspects causing implementation and opposition to the MCC agreement and analytical analysis is used to evaluate the datas and informations. This article studies on the balance of the possible benefits to Nepal and the obstacles faced by this global interconnection. Despite the ongoing heated debates, the MCC Compact has the potential to grant significant development benefits for Nepal if it is implemented with consideration for national sovereignty and peoples’ sentiment.